Snotwatch: an ecological analysis of the relationship between febrile seizures and respiratory virus activity - Rana Sawires; Martin Kuldorff; Michael Fahey; Hazel Clothier; Jim Buttery (BMC Pediatrics, 2022)
Abstract Background Febrile seizures are the commonest type of seizure in occurring in the first few years of life, mostly affecting children aged six months to five years old. While largely benign, the incidence of each febrile seizure increases the risk of recurrence, afebrile seizures and epilepsy. Viruses are the most frequent cause of febrile illnesses in which a febrile seizure occurs. Febrile seizure presentation patterns appear to follow a seasonal trend. Aims To identify patterns of febrile seizure incidence across different seasons with specific viral activity, and to establish a framework for analysing virus circulation data with common illnesses within a shared region and population. Setting Our study was a study of febrile seizure presentations in Victoria, Australia and respiratory virus detection. Participants We obtained independent datasets of emergency department febrile seizure presentations at Monash Health and all respiratory multiplex PCR tests performed at Monash Health from January 2010–December 2019 to observe common trends in virus circulation and febrile seizure incidence. Study design Trends were studied temporally through mixed effects Poisson regression analysis of the monthly incidence of febrile seizures and the rate of positive PCR tests. Peak viral seasons (95th centile incidence) were compared to median viral circulation (50th centile incidence) to calculate peak season risk ratios. Results We found a 1.75–2.06 annual risk ratio of febrile seizure incidence in June–September. Temporal analysis of our data showed this peak in febrile seizures was attributable to circulating viruses in this season, and virus modelling showed correlation with increased rates of positive Influenza A (1.48 peak season risk ratio), Influenza B (1.31 peak season risk ratio), Human metapneumovirus (1.19 peak season risk ratio) and Respiratory Syncytial Virus (1.53 peak season risk ratio) on PCR testing. Conclusion Our ecological study statistically demonstrates the recognised winter peak in febrile seizure incidence and ascribes the seasonal relationship to several viral infections which affect the community, including a novel association with Human metapneumovirus.